Norma geral antielisiva e desenvolvimento: diagnóstico, formulações normativas à prova e uma contribuição ao desenredo da regulação no Brasil - Souza, Bruno Nepomuceno de (2017)
The yearning for tax collection, to supply with funds the public coffers, and the freedom to organize the business, with the lowest tax burden as possible, polarized the interests of the government and the taxpayers. Almost a 'shelf product', tax planning has always been a broadly sold strategy. However, the State has changed, the values have changed, and the globalisation dramatized reality, highlighting that the legalistic perspective that had once underpinned with certainty the path through the legal loopholes, in fact, distorted the system, enhanced the non-compliance and tax evasion and, in various ways, jeopardized the tax equality. As an attempt to mitigate its effects, discreet and uncompleted steps were taken (in) in Congress, with the edition of a General Anti-Avoidance Rule, although deprived of regulation, (ii) in the case law, with foreigner innovations, in an endeavor to deal with the rule, and (iii) in the doctrine, to substantiate the postures, usually opposed to any step taken, either from a revenue or business bias. In the midst of all this, several attempts arose to regulate the so-called General Anti-Avoidance Rule. The study outlines, therefore, first and foremost, a terminological panorama with the related figures to the theme and an evolution of the debate in the doctrine. Thereafter, it’s revealed the behavior of the federal administrative court. Before the demands and international guidelines, it seeks to lead the debate to the global level, reasoning possible paradigms, to conclude if they would represent models to be transplanted. Soon after, it ranges the whole legislative construction around the issue, as tries of regulation. Ultimately, all the normative formulations are subjected to tests, on the basis of several criteria, with the intent of that, before the envisaged policy and founded on an argument of economic substance and reservations of business purpose, recommendations be provided for a regulation of the brazilian General Anti-Avoidance Rule.